2015
DOI: 10.1177/0959354315608705
|View full text |Cite
|
Sign up to set email alerts
|

Acting otherwise: Resistance, agency, and subjectivities in Milgram’s studies of obedience

Abstract: In this account of the Obedience to Authority experiments, we offer a richer and more dynamic depiction of the subjects' acts and reactions. To paraphrase Milgram, our account tries to examine the central elements of the situation as perceived by its research subjects. We describe a model of the experimenter-subject system that moves beyond experimentalism and humanism, positing instead a model that considers experimenter-subject relations and extends both spatially and temporally past the experiment's traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Third, resistance may be kept off the 'public balance sheet'. Hoffman et al (2015), for example, note that participants in Stanley Milgram's studies on obedience to authority consistently resisted calls to obey but that these acts were excluded from published reports. Acts which unsettle diagnostic practices in situ may, therefore, ultimately be disregarded.…”
Section: Introductionmentioning
confidence: 99%
“…Third, resistance may be kept off the 'public balance sheet'. Hoffman et al (2015), for example, note that participants in Stanley Milgram's studies on obedience to authority consistently resisted calls to obey but that these acts were excluded from published reports. Acts which unsettle diagnostic practices in situ may, therefore, ultimately be disregarded.…”
Section: Introductionmentioning
confidence: 99%
“…But while he used responses from the questionnaire data to defend himself against charges of unethical treatment of his subjects, he dismissed data from the same questionnaire when it appeared to challenge his conclusions on methodological grounds (Milgram, in Sabini and Silver 1992). Hoffman, Myerberg, and Morawski (2015:678) note that Milgram dismissed subject skepticism as a “defense function” and a “post facto explanation,” that is, an attempt by those who had obeyed to save face by denying any suffering occurred. Fearing contamination of the potential subject pool, Milgram did not conduct a formal debriefing of subjects until after 75 percent of those recruited had completed the experiment.…”
Section: Origins Of the Subject Questionnairementioning
confidence: 99%
“…Allied to this is the observation that the experimenter frequently departed from the standardized form of the prods in ways that rendered his interventions more akin to persuasive rhetoric than the exercising of blunt authority (Gibson, 2013a(Gibson, , 2013b. Secondary analysis of Milgram's studies has thus drawn attention to the levels of resistance and argumentation in the experiments (Gibson, 2013a(Gibson, , 2014(Gibson, , 2017Hoffman, Myerberg, & Morawski, 2015;Hollander, 2015;Hollander & Maynard, 2016) and has found that there are regularities in the timing of participants' attempts at defiance (Packer, 2008). Moreover, across all experimental conditions, defiance was more common than obedience (Haslam, Loughnan, & Perry, 2014).…”
Section: Rhetoric and Defiancementioning
confidence: 99%